Meningkatkan Aktivitas Dan Keterampilan Kolaborasi Siswa Menggunakan Model Pembelajaran Bakayuh Pada Mata Pelajaran IPA - Syarifah, Ari Hidayat (CV.ITTC INDONESIA, 2023)
The problem in this study lies in the low activity and collaboration skills of students in the content of Natural Sciences Theme 6 Heat and its Transfer. The purpose of this research is to describe the quality of students' activities and collaboration skills. This study used a quantitative approach with the type of Classroom Action Research (CAR) held in four meetings. The research subjects for Class V students at Barambai Kolam Kiri 3 Elementary School for the 2022/2023 school year totaled 20 students. The type of data in this research is qualitative and quantitative data through observation of students' activities and collaboration skills. Quantitative data was obtained through individual written test measurement techniques. Data analysis was carried out using a qualitative descriptive technique which was explained in tables and graphs presented with percentages as well as indicators of success and indicators of learning completeness that were determined. The results showed that the teacher's activity at meeting 4 obtained 92.5% achieving very good criteria. Student activity at meeting 4 obtained 85.71%. Collaboration skills at meeting 4 get 93%. Completeness of student learning outcomes in the classical meeting 4 obtains 100%.